2023
DOI: 10.1038/s41598-023-36838-2
|View full text |Cite
|
Sign up to set email alerts
|

Correlation analysis of hysterectomy and ovarian preservation with depression

Abstract: The relationship between hysterectomy and ovarian preservation and depression is controversial. This study aimed to determine the association of hysterectomy and ovarian preservation with depression using National Health and Nutrition Examination Survey. To assess the association between hysterectomy with or without ovariectomy and depression, we used 3 methods. Method 1: propensity score model (PSM) was established. Method 2 was logistics regression analysis of hysterectomy and depression before and after PSM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Inclusion criteria were simply 12 months of amenorrhea. In developed countries, hysterectomy, endometrial ablation incidence, is similar to the United States, and globally, 20% to 40% of women undergo hysterectomy by the age of 60 years 13 . What this means is that women were included in the study group and identified as being postmenopause, when they may have still been producing estrogen potentially accounting, at least in part, for the dramatically lower incidence of VMS.…”
mentioning
confidence: 99%
“…Inclusion criteria were simply 12 months of amenorrhea. In developed countries, hysterectomy, endometrial ablation incidence, is similar to the United States, and globally, 20% to 40% of women undergo hysterectomy by the age of 60 years 13 . What this means is that women were included in the study group and identified as being postmenopause, when they may have still been producing estrogen potentially accounting, at least in part, for the dramatically lower incidence of VMS.…”
mentioning
confidence: 99%